2018
DOI: 10.1080/14772000.2018.1483976
|View full text |Cite
|
Sign up to set email alerts
|

An updated phylogeny ofDeprea(Solanaceae) with a new species from Colombia: interspecific relationships, conservation assessment, and a key for Colombian species

Abstract: Deprea is a neotropical genus that comprises 51 species. Recent work based on molecular data has explored its monophyly and interspecific relationships, but the relationships amongst Deprea species were not entirely elucidated. The inclusion of more accessions and molecular markers in phylogenetic analysis is likely to produce more supported hypotheses. Therefore, the main objective of this study was to perform a combined phylogenetic analysis of Deprea including seven new samples representing six species and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In a prescient review, Hepper () pointed out that these two western African species, W. aristata and W. frutescens , are morphologically unlike others in Withania and suggested that their closest relatives may instead be across the Atlantic. Beyond the rearrangement of Withaninae necessitated by this apparent split within Withania , most of the genera that have been placed in the subtribe are monophyletic (or nearly so), based on extensive taxonomic work in recent years (Zamberlan et al., ; Deanna et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prescient review, Hepper () pointed out that these two western African species, W. aristata and W. frutescens , are morphologically unlike others in Withania and suggested that their closest relatives may instead be across the Atlantic. Beyond the rearrangement of Withaninae necessitated by this apparent split within Withania , most of the genera that have been placed in the subtribe are monophyletic (or nearly so), based on extensive taxonomic work in recent years (Zamberlan et al., ; Deanna et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Taxon coverage was 92.8% for ITS, 77.9% for LFY , 78.4% for waxy , and 87% for the chloroplast fragment (Appendix S3). DNA extractions were done following a modified 2 × CTAB procedure (Doyle and Doyle, ); primers and polymerase chain reaction conditions followed previous works (Smith and Baum, ; Deanna et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…In a prescient review, Hepper (1991) pointed out that these two western African species, W. aristata and W. frutescens , are morphologically unlike others in Withania and suggested that their closest relatives may instead be across the Atlantic. Beyond the rearrangement of Withaninae necessitated by this apparent split within Withania , most of the genera which have been placed in the subtribe are monophyletic (or nearly so) given extensive taxonomic work in recent years (Zamberlan et al, 2015; Deanna et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Taxa coverage was 92.8 % for ITS, 77.9 % for LFY, 78.4 % for waxy , and 87 % for the chloroplast fragment (Appendix S3). DNA extractions were done following a modified 2 x CTAB procedure (Doyle and Doyle, 1987); primers and PCR conditions followed previous work (Smith and Baum, 2006; Deanna et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation